Chemoinformatic-aided Antidiabetic Analysis of the Therapeutic Potential of Phytoconstituents in Eremomastax speciosa Extracts - Ibrahim, Sulyman Olalekan; Lukman, Halimat Yusuf; Ebhohimen, Israel Ehizuelen; Babamale, Halimah Funmilayo; Abdulkadir, Fatimah Ronke; Hamid, Abdulmumeen Amao; Zubair, Marili Funmilayo; Atolani, Olubunmi (Borneo Journal of Pharmacy, 2024)
This research attempts to establish the antihyperglycemic potential of Eremomastax speciosa, a medicinal plant utilized in traditional West African diabetes therapy, through virtual simulation. While numerous reports have validated its biological potency, studies on the drug-likeness and antidiabetic properties of its compounds are limited.  The in silico pharmacological, and toxicological profile of aqueous, methanolic/methylene phytochemicals from previously reported work was analyzed using Swiss ADME and Protox II online server. The docking process was performed using PyRx-0.8, coupled with AutoDock Vina. Phytochemicals that aligned with Lipinski’s rules for drugs were then subjected to a virtual docking simulation. This simulation replicated the inhibitory effects of E. speciosa phytochemicals on sodium-glucose co-transporters (SGLT2) and α-amylase, similar to metformin, an FDA-approved antidiabetic medicine utilized as a control. Phytochemicals such as 8, 9,10-dimethyltricyclo[4.2.1.1(2,5)]decane-9,10-diol (-6.6 kcal/mol), 11-isopropylidenetricyclo[4.3.1.1(2,5)]undec-3-en-10-one (-7.9 kcal/mol), 4-(1,5-dihydroxy-2,6,6-trimethylcyclohex-2-enyl)but-3-en-2-one (-7.3 kcal/mol), and N-methyl-N-4-[2-acetoxymethyl-1-pyrrolidyl]-2-butynyl]-acetamide (-7.5 kcal/mol) exhibits superior binding affinities to the specific proteins targeted, compared to metformin, implying that E. speciosa is a source of druggable antidiabetic molecules that can be enhanced to achieve better efficacy.